The Donbas Rift. Issue 1 (2nd January 2016) - Kudelia, Serhiy
Abstract : The "Russian Spring, " which was taken up in Donetsk and Luhansk as the struggle for the Donbas, led to the loss of the territory for both Ukraine and Russia. Although many blame Moscow for starting the war in the region, the key role was played by processes that took place within Ukraine. Violent revolution led to the government's loss of its monopoly on the use of force, polarized public opinion and produced counter-mobilization among its opponents. Oligarchs in Donbas hedged their bets trying to deal both with the new authorities and their local challengers. Members of security forces from the Donbas considered the new government illegal and supported separatism. Miscalculations by the government allowed the separatist movement room to consolidate, while the indiscriminate use of force by government troops increased support for the movement among the population. Russia exploited these developments, but did not play a determining role in them.